Penolakan Klausula Perpanjangan Kontrak Kerjasama Bangun Guna dan Serah - Jermia Edwaard Manoe; Miftakhul Huda (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Each contract is allowed to include a clause regarding contract extension, when the contract ends. The clause in the contract is that even though both parties have reached an agreement, the extension of the contract is not an obligation or achievement in the contract, for this reason if the construction and handover cooperation contract has ended and the service recipient hands over management to the government as the service user , refusing a request to extend the contract cannot be said to be a breach of promise or default. However, even though refusing to extend the construction and handover cooperation contract is the right of the service user, there needs to be a review if the contract period which is supposed to be long-term only stipulates a period of 7 (seven) years if it results in the contractor or pemodal as the service recipient being harmed.